ANALYSIS OF OLD AGE INSURANCE FINANCIAL STATEMENTS WITH EVA AND FVA METHODS AT BPJS EMPLOYMENT - Novania Trifana; Soulthan Saladin Batubara; Nur Hafizah Fatimah; Febrilia Amanda Hada; Angelina Br Capah (Universitas Efarina, 2021)
This study aimed to analyze the financial performance JHT (Old Age Security) as an effort in improving corporate profits and analyze methods of calculating EVA (Economic Value Added) and Financial Value Added (FVA) on financial ratios JHT (Old Age Security) on BPJS Employment. For the calculation of the financial statements commencing from December 2014 to June 2016. Of all the variable data is conducted quarterly financial calculations. EVA (Economic Value Added) is an effective tool commucation good for value creation that can be reached by the line manager who ultimately drives corporate performance and to connect with the capital markets. Which is included into the calculation of EVA is to calculate NOPAT, Calculating Cost of Debt, Counting the Cost of Equity, Calculating the Weighted Average Cost of Capital, and Counting Invested Capital. Then also through the method of calculation of Financial Value Added (FVA) is a new method for assessing performance and value-added enterprises. These methods consider the contribution of fixed assets in the company's net profit. The covering in the calculation FVA is Calculating NOPAT, Calculating Total Resources (TR), Calculating Depreciation Equivalent (ED), and Calculating the Financial Value Added (FVA). The results of the analysis of the hypothesis testing EVA partially affect financial performance which shows the EVA (Economic Value Added) a negative result in no added value to the company. it says that the company is not healthy, so it can be detrimental to the company. For FVA (Financial Value Added) showed a positive influence to create added value for the company. Then to the results of hypothesis testing to two (2) EVA (Economic Value Added) has no effect simultaneous to the increase in financial performance due to EV negative, but for the FVA (Financial Value Added) influence simultaneously against the company due to a positive effect and provide added value against the company..